EKSPLORASI DAN IDENTIFIKASI GULMA, HIJAUAN PAKAN DAN LIMBAH PERTANIAN YANG DIMANFAATKAN SEBAGAI PAKAN TERNAK DI WILAYAH LAHAN KERING LOMBOK UTARA - Ni Made Laksmi Ernawati; I Ketut Ngawit (Buletin Peternakan, 2015)
Difficulties on weeds control and fodder scarcity in dry season are the major problems at dry land. Aim of this research was to identify and to explore the potency of several kinds of weeds, forages, and agricultural wastes that can be used as fodder, and further might be processed to make hay and silage. Explorative research to identify, observe, and collect data has been done using descriptive method of dominant weeds, forages, and agricultural waste that frequently used as fodder by farmers. The farmer’s decision to use weeds, forages, and agricultural wastes were determined by preference level of cattles and farmers empirical experiences. Result showed that dominant weeds found were broad leafed weeds with domination level 34.62-81.45% and narrow leafed weeds (grasses and teki) with domination level 28.65-65.38%. Broad leafed weeds that generally used as fodder were Cintella asiatica, Amaranthus spp., Mikania sp., Cyclosorous aridus, Gleichenia linearis, Physalis angulata, Portulaca oleracea, Mucaena pruriens, and Desmodium scalpe. Grasses weeds and teki were potential fodder with preference level of cattle from very much like to extremely like. Forage and agricultural waste that be potential as fodder were gamal leaf, sengon leaf, banana leaf and stem and coconut, agricultural waste of peanuts, corn, and sweet potato.(Key words: Animal feed, Agricultural wastes, Dry land, Fodder, Forage, Identification and exploration, Weeds)